(untitled) (KYAMC Journal, 2026)
Background: Adult early-onset type 2 diabetes mellitus (T2DM), is increasing worldwide, including Bangladesh. The clinical characteristics and patterns of complications differ significantly between adult early-onset (<40 years) and usual-onset (≥40 years) type 2 DM. Objectives: This study aimed to describe the clinical characteristics of adult early-onset T2DM in Bangladeshi patients and to identify associated risk factors. Materials and Methods: This cross-sectional study was carried out including 185 T2DM patients in an outpatient settings. Clinical characteristics, probable risk factors, and laboratory findings were collected from patients’ history and medical records. Participants were categorized into early-onset (<40 years) and usual-onset (≥40 years) groups. Data were analyzed using percentages, mean ± standard deviation, independent sample t-test, Chi-square test, and multivariate regression analysis where appropriate. Results: Early-onset T2DM accounted for 41.6% of cases, while 58.4% were usual-onset. The mean age at diagnosis of DM in the early-onset group was 33.66 ± 4.08 years. Higher educational status, longer duration of diabetes, poor glycemic control (HbA1c ≥8%), and higher fasting blood glucose levels were significantly more common among early-onset patients. Early-onset DM was significantly associated with increasing HbA1c categories. Family history of diabetes, obesity, and hyper triglyceridemia were more frequent in the early-onset group. Most vascular complications were more prevalent in the usual-onset group, except peripheral neuropathy, which was more common in early-onset patients. Conclusion: Type 2 diabetes is emerging as a significant health concern among young adults in Bangladesh. Early diagnosis and effective glycemic control are crucial to reduce long-term complications and disease burden.